(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2023)
Today learning foreign languages are being global all over the world. So, there we can see a lot of new methods and technologies to teach the foreign languages effectively. This article also analyzes some games to teach English language better in the classroom.